Organization's image as the main factor of its competitiveness - Klimova, A. S. (ТДАТУ, 2020)
The purpose of this article is to determine the role and importance of image, research tools used to create the image of the enterprise to increase its competitiveness.
Keywords: PR - services Public Relations; importance of image; image of the enterprise